Βιβλιοκρισία:S. RONCHEY, Hypatia. The True Story. English translation by Nicolò Sassi. With the collaboration of Giulia Maria Paoletti, Berlin - Boston: De Gruyter 2021 - ΚΑΡΛΑ, Γραμματική (Byzantina Symmeikta, 2022)
Βιβλιοκρισία:S. RONCHEY, Hypatia. The True Story. English translation by Nicolò Sassi. With the collaboration of Giulia Maria Paoletti, Berlin - Boston: De Gruyter 2021